Effect of cement stabilized peat on strength, microstructure, and chemical analysis - Wahab, Norhaliza; Abu Talib, Mohd Khaidir; Madun, Aziman; Abd Malik, Ahmad Khairul (Elsevier, 2023)
Adding Ordinary Portland Cement (OPC) to alter peat properties has been established in some research, but its mechanism in strength gain is less studied. Therefore, understanding on the strength gain and chemical effect in cement stabilized peat is essential to be further investigated. An extensive laboratory tests were performed to correlate the strength performance with chemical compound and soil structure behaviour after stabilization. Three types of peat which is fibric (PF), hemic (PH) and sapric (PS) were stabilized with various cement dosage of 300–500 kg/m3 at 7 and 28 days. The stabilized peats strength was observed via the Unconfined Compressive Strength (qu) test with the target strength 50 kPa. The X-ray Diffraction (XRD) and Scanning Electron Microscopy-Energy Dispersive Spectroscopy (SEM-EDS) were conducted to verify morphological formation and chemical compounds during stabilization. The results showed the optimum cement dosage 300, 400, and 500 kg/ m3 for fibric, hemic, and sapric peat was sufficient to achieve the target strength of 73.69, 53.48, and 59.37 kPa at 28 days, respectively. For comparison, fibric and hemic peat had higher strength than sapric peat, simulta¬neously with the increasing of cement dosage and curing period, which could be affected by the degree of decomposition. Finally, the strength of stabilized peat increased with an increase in cement dosage and curing days. In contrast, the carbon significantly reduced, and calcium oxide increased with the formation of cemen¬titious products such as Calcium Silicate Hydrate (CSH). Thus, cement is a good binder to improve peat prop¬erties through strength and chemical analysis results.